2022
DOI: 10.1016/j.jss.2021.111197
|View full text |Cite
|
Sign up to set email alerts
|

Changes in perceived productivity of software engineers during COVID-19 pandemic: The voice of evidence

Abstract: Background: The COVID-19 pandemic triggered a natural experiment of an unprecedented scale as companies closed their offices and sent employees to work from home. Many managers were concerned that their engineers would not be able to work effectively from home, or lack the motivation to do so, and that they would lose control and not even notice when things go wrong. As many companies announced their post-COVID permanent remote-work or hybrid home/office policies, the question of what can be expec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 21 publications
1
40
0
1
Order By: Relevance
“…Smite et al revealed that during WFH context, software engineers continue committing code and carry out their daily duties without significant disruptions [11]. This also aligns with findings that developers are found least impacted by the new situation.…”
Section: Po9mentioning
confidence: 53%
See 3 more Smart Citations
“…Smite et al revealed that during WFH context, software engineers continue committing code and carry out their daily duties without significant disruptions [11]. This also aligns with findings that developers are found least impacted by the new situation.…”
Section: Po9mentioning
confidence: 53%
“…Smite et al studied 13 surveys in the literature finding that on average perceived productivity had not changed significantly, there are developers who report being more productive, and developers are less productive when working from home [11]. Also, positive trends are found in longitudinal surveys, i.e., developers' productivity in the later months of the pandemic show better results than those in the earlier months.…”
Section: Work From Home and Software Engineeringmentioning
confidence: 99%
See 2 more Smart Citations
“…The COVID-19 event threatened companies' existing resources, disrupted work routines, and caused employees to complain about digital technology challenges related to team and collaboration, as well as mood, distractions, which meant working at home Jobs may not be for everyone (Smite et al, 2022). Dramatic changes in work patterns may ultimately reduce their propensity to express voice and increase silence (Wee & Fehr, 2021).…”
Section: Introductionmentioning
confidence: 99%